Comparative study of post-sintering temperature on properties of copper doped zinc oxide nanoparticles prepared by co-precipitation process - Chaithanatkun, Natpasit; Onlaor, Korakot; Tunhoo, Benchapol (My University, 2017)
Copper doped zinc oxide nanoparticles (Cu doped ZnO NPs) has been prepared by co-precipitation process using zinc nitrate, copper nitrate and potassium hydroxide as zinc, copper and hydroxide precursor, respectively. All of prepared conditions were fixed as the concentration of copper in zinc oxide about atomic percentage at 2%. The prepared powders of Cu doped ZnO NPs were studied with various post-sintering temperature at 500, 600 and 700 °C. All of samples were characterized using X-ray Diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX) and Fourier transform infrared spectroscopy (FT-IR). The EDX spectra showed the qualitative and quantitative elemental composition of prepared material, meanwhile, XRD peaks represented Cu doped ZnO NPs in hexagonal wurtzite structure. The improvement in crystallinity of Cu doped ZnO NPs could be performed by sintering process. Moreover, the SEM and TEM images showed that the Cu doped ZnO NPs were condensed to the larger particles size by the increase of sintering temperature. Finally, the FT-IR spectra showed a broad absorption band for all of samples.
Keywords: Co-precipitation; Copper doped zinc oxide; Sintering temperature